Second Generation Biorefineries. A Contribution To The Syngas And Lignins Platforms - Moreira, Rui Estevão Silva de Jesus (2020)
PhD Thesis in Chemical Engineering submitted to the Faculty of Sciences and Technology of the University of Coimbra